2016
DOI: 10.1038/ncomms13044
|View full text |Cite
|
Sign up to set email alerts
|

Novel near-infrared emission from crystal defects in MoS2 multilayer flakes

Abstract: The structural defects in two-dimensional transition metal dichalcogenides, including point defects, dislocations and grain boundaries, are scarcely considered regarding their potential to manipulate the electrical and optical properties of this class of materials, notwithstanding the significant advances already made. Indeed, impurities and vacancies may influence the exciton population, create disorder-induced localization, as well as modify the electrical behaviour of the material. Here we report on the exp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

10
58
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 65 publications
(69 citation statements)
references
References 25 publications
10
58
0
Order By: Relevance
“…We suggest that spectra at lower energies than the intrinsic band gap of MoO 3 ascribed to excited electron–hole pairs recombination at lower energy states because of electron–phonon scattering was occurred by high‐energy electron beam of CL. In contrast, almost identical invisible spectra from the nanosheet and petal of flower are observed, which pronounced the presence of MoS 2 because the nonradiative recombination occurred after relaxation of an excited electron from the conduction band to valance band . These results from CL analysis are in good agreement with the results from XRD and Raman.…”
Section: Resultssupporting
confidence: 82%
“…We suggest that spectra at lower energies than the intrinsic band gap of MoO 3 ascribed to excited electron–hole pairs recombination at lower energy states because of electron–phonon scattering was occurred by high‐energy electron beam of CL. In contrast, almost identical invisible spectra from the nanosheet and petal of flower are observed, which pronounced the presence of MoS 2 because the nonradiative recombination occurred after relaxation of an excited electron from the conduction band to valance band . These results from CL analysis are in good agreement with the results from XRD and Raman.…”
Section: Resultssupporting
confidence: 82%
“…Dhall et al observed a remarkable increase in exciton emission intensity in many‐layer MoS 2 flakes through a gentle oxygen plasma etching treatment . Fabbri et al observed enhanced near‐infrared emission in MoS 2 multilayer flakes via engineering crystal defects . Li et al obtained enhanced electroluminescence from multilayer MoS 2 via an electrical modulation method .…”
Section: Introductionmentioning
confidence: 99%
“…Through the use of electron energy‐loss spectroscopy (EELS), it is further proved that there are S and N in the doped graphene lattice, as summarized in Figure i. Besides C‐ K edge (excitation of 1s carbon electrons to π* states at ≈286 eV and 1s to σ* states at ≈294 eV), the doped graphene films are also found to have S‐ L edge at 169 eV and N‐ K edge at 403 eV . As displayed in Figure j–l (EELS elemental maps), C, N, and S exhibit uniform spread in graphene, and extensive SAED patterns (Figure S5, Supporting Information) show a remarkable domain size of doped graphene films .…”
Section: Resultsmentioning
confidence: 86%